An integrated process of calcium hydroxide precipitation and air stripping for pretreatment of flue gas desulfurization wastewater towards zero liquid discharge. (10th September 2021) - Cheng, Qingfeng; Wu, Yalan; Huang, Yang; Li, Fengjiao; Liu, Zongyang; Nengzi, Lichao; Bao, Linlin
Abstract: Flue gas desulfurization wastewater (FGDWW) is produced during flue gas desulfurization process in coal-fired power plants. It has a complex composition and high pollutant concentration and is harmful to the environment. The Chinese government has regulated the zero liquid discharge (ZLD) of FGDWW. To achieve this, an integrated process of calcium hydroxide precipitation and air stripping for the pretreatment of FGDWW was developed in this study. Ca 2+ and OH − were added in the calcium hydroxide precipitation step and reacted with SO4 2−, F − and Mg 2+ in the real FGDWW to form precipitates for removal. The SO4 2− concentration was lower than the detection limit at pH 4, and the F − and Mg 2+ concentrations were reduced to 4 and 46 mg/L at pH 11, respectively. The NH4 + concentration decreased to 7.86 mg/L after air stripping for 120 min at pH 11. The excess Ca 2+ was removed by further stripping, and the pH value decreased to about 8.0. The F − and NH4 + removal rates were significantly higher in the real than the simulated FGDWW. After the pretreatment, the concentrations of SO4 2−, F −, Mg 2+, NH4 +, Ca 2+, total dissolved solids (TDS), and chemical oxygen demand (CODCr ) in the real FGDWW decreased to 0.00, 1.5, 20.35, 8.26, 8.61, 8260 and 86 mg/L, and the corresponding removal rates were 100.00%, 97.50%, 99.59%, 96.43%, 98.97%, 78.48% and 94.29%, respectively. The molar concentration ratio of Cl − and Na + changed from 3.14:1 in the raw FGDWW to 1.02:1 in the pretreated FGDWW by adding Na2 CO3 in the air stripping step to reduce membrane fouling in the reverse osmosis (RO) process. The treated FGDWW could be recycled, and the by-products (gypsum, (NH4 )2 SO4, CaCO3 and NaCl) could be utilized. This technology achieved ZLD of FGDWW, representing a clean pathway and promoting the sustainable development of the power industry. The added chemicals did not remain in the pretreated FGDWW, adhering to with the principle of cleaner production. The pretreatment technology exhibited not only high removal efficiency for the main pollutants, but also low operational cost and convenient automatic control. Graphical abstract: Image 1 Highlights: SO4 2−, F −, Mg 2+, NH4 +, Ca 2+ and CODCr were simultaneously removed from FGCWW. The treated FGCWW could be recycled and zero liquid discharge of FGCWW was achieved. The pretreatment process was in line with the concept of cleaner production. The by-products could be recovered by stages and utilized as resources. The pretreatment technology exhibited high removal efficiency and low operation cost.